Demographic change and climate change. (27th February 2020) - Rauscher, Michael
Abstract: This paper uses a continuous-time overlapping-generations model with endogenous growth and pollution accumulation over time to study the link between longevity and global warming. It is seen that increasing longevity accelerates climate change in a business-as-usual scenario without climate policy. If a binding emission target is set exogenously and implemented via a cap-and-trade system, the price of emission permits is increasing in longevity. Longevity has no effect on the optimal solution of the climate problem if perfect intergenerational transfers are feasible. If these transfers are absent, the impact of longevity is ambiguous.